On (q2 + q + 1)-sets of class [1, m, n]2 in PG(3, q) - Napolitano, Vito (Journal of geometry, 2014)
A characterization of cones in P G (3, q ) as sets of points of P G (3, q ) of size q 2 + q + 1 projecting from a point V a set of q + 1 points of a plane of P G (3, q ) and with three intersection numbers with respect to the planes is given.